An intraoperative MRI system for margin assessment in breast conserving surgery: Initial results from a novel technique. Issue 1 (15th April 2016) - Papa, Moshe; Allweis, Tanir; Karni, Tami; Sandbank, Judith; Konichezky, Myriam; Diment, Judith; Guterman, Assaf; Shapiro, Moshe; Peles, Zachi; Maishar, Roi; Gur, Assaf; Kolka, Eyal; et al.
Abstract : Background and Objectives: One of the major unmet needs in Breast Conserving Surgery (BCS) is a rapid and accurate margin assessment of the lumpectomy specimen. This study evaluates the ability of a novel MRI system (prototype of the ClearSight™ system; Clear‐Cut Medical Ltd., Rehovot, Israel) to distinguish malignant and non‐malignant tissues in freshly excised breast specimen by comparing MR measurements to histopathology results. Methods: Seventy‐seven samples were obtained from 22 patients undergoing BCS enrolled in the study. A T2* (T2 Star) value in milliseconds (ms) was calculated for each sample and correlated with histopathology results. Results: Of the 77 samples, 35 samples were classified by histopathology as malignant and 42 as non‐malignant. T2* values were significantly higher in malignant samples compared to non‐malignant samples (15.3 ± 2.72 ms and 10.6 ± 1.47 ms, respectively [ P < 0.00001]). Analysis for a determined cutoff of 11.7 ms revealed 91% sensitivity, 93% specificity, and 92% accuracy. ROC curve analysis yielded AUC of 0.97. Conclusions: This study demonstrates that the system is sensitive and specific in differentiating malignant and non‐malignant tissues in freshly excised breast specimen. The system has the potential to be used for breast specimen margin assessment during BCS, with the goal of decreasing the need for re‐operation. J. Surg. Oncol. 2016;114:22–26 . © 2016 Wiley Periodicals, Inc.